2015
DOI: 10.1186/s40064-015-1111-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of coping with interpersonal stress on the risk of depression in a Japanese sample: a focus on reassessing coping

Abstract: Reassessing coping, a concept first proposed in Asia, refers to efforts to wait patiently for an appropriate opportunity to act or for a change or improvement in a situation, and can be observed in individuals facing stressful relationship events. The main purpose of the present study was to determine if reassessing coping would be associated with a lower risk of depression. The author examined the relationships between depression risk using the Center for Epidemiologic Studies Depression Scale (CES-D) and cop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 24 publications
4
12
1
Order By: Relevance
“…In the analyses, given that significant gender differences in depression (Kato, 2015b) and loneliness (Moroi, 1991) have been found in Japanese college samples, gender (male 1, female 2) was entered as a control variable in Step 1. Then, three coping strategies were entered in Step 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the analyses, given that significant gender differences in depression (Kato, 2015b) and loneliness (Moroi, 1991) have been found in Japanese college samples, gender (male 1, female 2) was entered as a control variable in Step 1. Then, three coping strategies were entered in Step 2.…”
Section: Resultsmentioning
confidence: 99%
“…It has been confirmed that constructive coping usually has nothing to do with mental health problems such as depression and loneliness, distancing coping is positively associated with such problems, and reassessing coping is negatively related to them (e.g., Kato, 2013Kato, , 2015aKato, , 2015bTaniguchi, 2017). Depression is a key example of a consequence of stress and coping processes among adolescents (Compas, Orosan, & Grant, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Postponed-solution coping gives people the time necessary to control their emotions, to see their own situation from different perspectives, and to understand the situation better. Thus, such coping enables people to behave calmly in the stressful situation and to accept the circumstance, and the calm and receptive behavior, in turn, reduces their psychological distress (Kato, 2013(Kato, , 2014(Kato, , 2015a(Kato, , 2015b. For instance, people might be excited immediately after a quarrel but could restore their mental balance by taking time, and, as a result, they could select the most effective strategy with the situation (Kato, 2015b).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, such coping enables people to behave calmly in the stressful situation and to accept the circumstance, and the calm and receptive behavior, in turn, reduces their psychological distress (Kato, 2013(Kato, , 2014(Kato, , 2015a(Kato, , 2015b. For instance, people might be excited immediately after a quarrel but could restore their mental balance by taking time, and, as a result, they could select the most effective strategy with the situation (Kato, 2015b). Unlike interpersonal blunders and interpersonal friction, which stem from self-criticism and concerns regarding one's own treatment toward his/her partner (Hashimoto, Mojaverian, & Kim, 2012), interpersonal conflict (explicit conflict, quarreling, or discord) is caused partly by factors beyond one's control such as his/her partner's personality and value.…”
Section: Discussionmentioning
confidence: 99%
“…Kato (2015) showed CES-D score of college students in Kanto Region (Men: M ¼ 17.53, SD ¼ 10.69; Women: M ¼ 18.86, SD ¼ 10.02) and suggested that CES-D scores of Japanese college students are often higher than samples from other countries. Moreover, another study (Kobayashi, Kobayashi, Kubo, Sonoda, & Mori, 2005) using college students in Hokkaido showed that the CES-D total score was 19.1 (SD ¼ 9.0), relatively high compared to that of college students in Kanto Region (Kato, 2015). One possible reason for this may be the short days in winter (Aries, Aarts, & Hoof, 2015).…”
Section: Limitations and Conclusionmentioning
confidence: 99%